2012
DOI: 10.1590/s0102-33062012000200014
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias no uso da energia luminosa por plantas jovens de Genipa spruceana Steyerm submetidas ao alagamento

Abstract: Na tentativa de elucidar estratégias de utilização da energia luminosa em plantas jovens de Genipa spruceana Steyerm submetidas ao alagamento, nós investigamos a capacidade de captura e uso de energia luminosa em G. spruceana sob três condições de crescimento: 1- ausência de alagamento (SA), 2- plantas parcialmente alagadas (PA) e 3- plantas totalmente alagadas (TA). Medidas de área foliar específica, teores de pigmentos cloroplastídicos e fluorescência da clorofila a foram feitas em intervalos regulares no pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
(43 reference statements)
0
11
0
1
Order By: Relevance
“…In Aloysia gratissima (Gill et Hook) Tronc., a significant effect was observed in root dry matter of plants grown in full sun and shaded by 40 and 80% with Aluminet® screens, obtaining values of 32.8, 43.8, and 15.8 g, respectively (Pinto et al, 2007). According to Gonçalves et al (2012), plants that grow in full sun present higher transpiration flows and require larger and more efficient root systems, with a better developed vascular system.…”
Section: Resultsmentioning
confidence: 99%
“…In Aloysia gratissima (Gill et Hook) Tronc., a significant effect was observed in root dry matter of plants grown in full sun and shaded by 40 and 80% with Aluminet® screens, obtaining values of 32.8, 43.8, and 15.8 g, respectively (Pinto et al, 2007). According to Gonçalves et al (2012), plants that grow in full sun present higher transpiration flows and require larger and more efficient root systems, with a better developed vascular system.…”
Section: Resultsmentioning
confidence: 99%
“…Gonçalves et al (2012) suggested that the flow of light energy into G. spruceana seedlings under total flooding, at the beginning, it was more restricted by a light harvesting structure decrease than in the functioning of the photosynthetic complex. Similarly to these authors, was observed differences between the density of molecules in the reaction center and the time of experimentation.…”
Section: Resultsmentioning
confidence: 99%
“…Stress caused to plants by the influence of an environment different from that to which they are adapted reflects in anatomical, morphological, and physiological changes (Gonçalves et al, 2012;Ismail et al, 2012). Thus, acclimatization capacity of a species is a key point in maximizing resources essential for survival under these conditions (Dias-Filho and Carvalho, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in the accumulation of root, stem, and branch biomass, formation of adventitious roots and aerenchyma/pneumatophores, leaf expansion, or induction of leaf abscission are some of the main responses evidenced by water stress on susceptible plants (Colmer and Pedersen, 2008). Susceptible species at more advanced stages submitted to soil flooding showed more intense stress symptoms, such as leaf yellowing related to the degradation or decrease of their synthesis by low nitrogen uptake in the roots, which leads to photoinhibition, necrosis, and tissue death (Gonçalves et al, 2012).…”
mentioning
confidence: 99%